Cybercrime as Transnational Crime: Law Enforcement and Countermeasure Problems in the Perspective of International Criminal Law - Banjarani, Desia Rakhma; Rahmadhani, Muhammad Apriliansyah (Yustisia Tirtayasa : Jurnal Tugas Akhir, 2024)
Today's interconnected world, cybercrime is a pressing global issue that transcends national borders, rendering domestic legal frameworks inadequate. Despite the significant losses from cybercrime within its borders, Indonesia has not yet ratified the 2001 Convention on Cybercrime, a key international legal instrument. This research addresses this urgent issue by examining Indonesia's current approach to combating transnational cybercrime and evaluating it from the perspective of international criminal law. Employing a normative legal research methodology with case and legislative approaches, this study reveals that Indonesia's efforts are hampered by complex challenges related to jurisdiction, legal frameworks, and enforcement. Our findings emphasize the critical need for Indonesia to address these issues by adopting an international legal perspective. The study's main contribution is to propose a path forward: the development of comprehensive legal instruments—such as ratifying the Convention on Cybercrime—alongside strengthened international cooperation through information sharing, training, and technical assistance. This provides a novel framework for Indonesia to more effectively combat cybercrime.